Hubungan Riwayat Hipertensi, Riwayat Keturunan dan Obesitas dengan Kejadian Preeklamsi Pada Ibu Hamil - Silaban, Titin Dewi Sartika; Rahmawati, Eka (JOURNAL OF MIDWIFERY SCIENCE, 2025)
Preeclampsia is a disease with signs of hypertension, edema, and proteinuria arising from pregnancy. This disease generally occurs in the 3rd trimester of pregnancy, but can occur earlier, for example in a hydatidiform moleTo find out whether there is a relationship between a history of hypertension, a history of heredity and obesity with the incidence of pre-eclampsia in pregnant women. This type of research is quantitative using an Analytical Survey with a Cross Sectional approach, where the independent variable (history of hypertension, history of heredity and obesity) and the dependent variable (incidence of pre-eclampsia). The population in this study were 1,980 pregnant women who had their pregnancy checked. The sample in this study was carried out by random sampling with the simple random sampling method. Data analysis used univariate analysis and bivariate analysis. The results of the univariate analysis showed that there were 17.9% fewer people with preeclampsia than those without preeclampsia, which was 82.1%. While the results of the chi square test showed that there was a relationship between a history of hypertension and the incidence of preeclampsia with p value = 0.000, there was a relationship between heredity and the incidence of preeclampsia with p value = 0.000, and there was a relationship between obesity and the incidence of preeclampsia with p value = 0.020. Relationship history of hypertension, history of heredity, and obesity with the incidence of preeclampsia.